Third Year Winner: Charity Analysis: The Boundless School: WRIT 3710, Introduction to Institutional Writing. Course Director: Marlene Bernholtz - Lynar, Rachel (Jan Rehner Prize for Writing, 2016)
Rachel Lynar, author of “Charity Analysis: The Boundless School,” was asked to “produce a report that introduces the charity and indicates briefly why it would or would not be a good fit for a York University sponsorship/partnership.” As one assessor noted, “the author clearly understood what they were asked to do and completed the task.” The report, which recommends a university partnership with “The Boundless School” is well-written and entirely convincing. Its research is comprehensive, and its choice of partners is likely to be highly attractive to decision-makers in the university environment. This third year assignment favourably compares with other professional reports, such that the University would do well to consider the proposals here, and, as the report recommends, “partner with Boundless long-term.”